Neuropathic pain - Attal, N.; Bouhassira, Didier (New York, NY : Oxford University Press, 2023)
This volume uses a case-based approach to cover important topics in the examination, investigation, management, and treatment of various types of neuropathic pain.
Also issued in print: 2023.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 3, 2023).
Keywords: Nervous system -- Diseases -- Case studies; Pain -- Treatment -- Case studies; Health and Wellbeing; Clinical & internal medicine